PENGARUH MOTIVASI RENDAH BIAYA DAN KEPEMIMPINAN TERHADAP KOMITMEN KERJA - Manek, Aquidowaris; Manane, Desmon Redikson; Huda, Nurul; Kase, Yakoba A. E. R. (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
ABSTRACT The stanting problem in North Central Timor Regency has increased. The data shows that the highest number is at the Manumean Health Center at 28.3% and the lowest at the Lurasik Health Center at 19.7%. This is indicated due to weak work commitment. This study aims to determine the partial and simultaneous effect of low-cost motivational variables (X1) and leadership variables (X2) on work commitment to the stunting reduction acceleration team in TTU Regency. This study focuses on all teams for the acceleration of stanting reduction and in the field of family health and nutrition at the TTU District Health Office with a total of 40 respondents. The data analysis technique used is inferential analysis. The results of inferential analysis show that the low-cost motivation variable (X1) has a significant influence on work commitment (Y). The leadership variable (X2) has a significant effect on work commitment (Y). Meanwhile, the low cost motivation variable (X1) and the leadership variable (X2) simultaneously have a significant effect on work commitment. Keywords: Low Cost Motivation, Leadership, and Work Commitment